FAKTOR YANG BERPENGARUH TERHADAP MARGIN MURABAHAH PADA BANK SYARIAH MANDIRI PERIODE 2013-2015 - Anik Anik (Jurnal Ilmiah Ekonomi Islam, 2017)
The purpose of this study was to determine the factors that  effect the revenue margin murabaha in Bank Syariah Mandiri as well as to identify factors that significantly influence the revenue margin murabaha. Data analysis technique used is using multiple linear regression. The population used in this study the financial statements of Bank Syariah Mandiri. Sampling with saturated sampling method. This study using the Statistical Product and Service Solution (SPSS) version 16. The results using the F test showed that simultaneous independent variable profitability, third party funds, the overhead, the BI rate and the inflation effect on revenue margin murabaha. Partial results obtained using the t test profitability, third party funds, overhead, BI rate effect on revenue margin murabaha. This is evidenced by a smaller significance level of 0.05 is the profitability of 0.006, third party funds 0.049, 0.049 overhead costs, BI rate 0.003. While inflation variable does not effect the revenue margin murabaha with significance of 0.642 is greater than0.05. Adjust R square the value for 0.424 indicate that revenue murabaha margin can be explained by any study variable, while the rest is explained by other factors that are not included in the study.